Ketidkpastian Lingkungan dan Keberlanjutan: Efek Moderasi Efisiensi Inovasi - Kushermanto, Andi; Alisa, Inayah Risqi; Sari, Reni Mustika; Shafarani, Dinda Ayu; Zulfania, Hana; Tri, Nguyen Huu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study examines the influence of environmental uncertainty on sustainable growth and the moderating effect of innovation efficiency in this relationship. The population of this study is Sharia rural banks in Central Java for the 2018–2022 period. The sample of this study obtained through the purposive sampling method has 25 Sharia rural banks that meet the criteria. The data analysis technique used is partial least squares structural equation modelling (PLS-SEM) using WarPPLS version 8.0 software. This study shows that environmental uncertainty negatively and significantly affects sustainable growth. The effects of environmental uncertainty can damage the company's sustainability. Furthermore, the moderating test shows that innovation efficiency weakens the influence of environmental uncertainty on sustainable growth. This study provides evidence of the importance of innovation efficiency in maintaining the Sharia rural bank's sustainable growth in an uncertain environment. The findings will be helpful for the Sharia rural bank managers to optimize IT strategy through research and development implementation in their strategic planning and continuously enhance their innovation efficiency to manage the adverse effects of environmental uncertainty.